Vitomil Zupan i Borislav Pekić - Milanović, Željko (Slavistična revija, 2014)
The literary works Levitan by Vitomil Zupan and Godine koje su pojeli skakavci (The Years the Locusts Have Devoured) by Borislav Pekić are poetically similar narratives of their authors' prison experience. Both authors chose the genre for their works based on the initial narrative situation in which their main character/narrator is placed, i.e., the situation that does not seem to have much narrative potential. The paper shows how Zupan and Pekić - who were both aware that their works dealing with personal prison experience cannot expect a welcome reception - selected a genre in which personal experience shifts to general, but without losing the perspective of authenticity of the experience.
Keywords: "Godine koje su pojeli skakavci"; "Levitan"; novel; Pekić, Borislav, 1930-1992; primerjalne študije; recepcija; roman; Slovene literature; slovenska književnost; srbska književnost; zapor; Zupan, Vitomil, 1914-1987